Validation of a manual protocol for BRAF V600E mutation-specific immunohistochemistry - Dinges, Hanns-Christian; Capper, David; Ritz, Olga; Brüderlein, Silke; Marienfeld, Ralf; Deimling, Andreas von; Möller, Peter; Lennerz, Jochen K. (Applied immunohistochemistry & molecular morphology, 2015)
Detection of BRAF V600E has diagnostic, prognostic, and therapeutic relevance. The recently developed BRAF V600E mutation-specific antibody has evolved into a feasible alternative to DNA analysis. The plethora of immunohistochemical protocols makes implementation tedious and, here we tested a set of manual and automated protocols and compared test performance with sequencing results. For assays, we employed formalin-fixed, in part decalcified, and paraffin-embedded tissue samples. Empiric testing of manual protocols included 10 variables in 17 protocols. Automated immunohistochemical staining and BRAF pyrosequencing served as independent test methods. Test performance measures were compared without considering 1 method as a standard. Four well-fixed samples (2WT/2Mut) were used for testing of all protocols and indicated 2 correctly classifying procedures. Practical performance assessment employed 33 independent tissue samples, composed of 27 leukemias (by pyrosequencing: 8 wild-type; 18 mutated; 1 noninformative) and 6 melanomas (V600E; V600K; wild-type, 2 each). Manual V600E staining was positive in 20 cases (19 of 20 V600E-containing samples plus the 1 sample that was noninformative), whereas all wild-type and V600K cases were immunonegative. Manual or automated staining as well as pyrosequencing would have missed an equal number of V600E-mutated cases and the correlation coefficient for these methods was 0.75 to 0.93 (substantial to almost perfect); the Youden index was 0.95. Detection of V600E-mutated BRAF at the protein level in routine and decalcified tissue samples is possible, and the presented manual protocols should expedite implementation in routine diagnostic practice. Our results indicate that both molecular techniques should be considered complementary.